58.7k views
0 votes
PLEASE HELP I PUT THE PROBLEM AS A PICTURE PLEASE ANSWER WILL GIVE 30 POINTS SHOW WORK

PLEASE HELP I PUT THE PROBLEM AS A PICTURE PLEASE ANSWER WILL GIVE 30 POINTS SHOW-example-1
User Affaz
by
4.8k points

1 Answer

4 votes

Answer:


\huge\boxed{9}

Explanation:


\sf (2^8 * 3^(-5) * 6^0)^(-2 ) ((3^(-2))/(2^3) )^4*2^(28)

Rule of exponents
a^0 = 1 ,
1/a^m = a^(-m)

=>
\sf 2^(8*-2) * 3 ^(-5*-2) * 3 ^(-2)* 2^(-3*4) * 2^(28)

=>
\sf 2 ^ {-16} * 3^(10) * 3^(-8) * 2 ^(-12)* 2^(28)

Combining same bases

=>
\sf 2 ^ {-16} * 2 ^(-12)* 2^(28)* 3^(10) * 3^(-8)

When bases are same , powers are to be added

=>
\sf 2 ^(-16-12+28) * 3^(10-8)

=>
\sf 2^(-28+28) * 3^2

=>
\sf 2^0 * 3^2

=>
\sf 3^2

=> 9

User Tom Jenkin
by
4.9k points